# given that 3x-5y=7, what is (6-3x+5y)+(6-3x+5y)^2+..........+(6-3x+5y)^2002?

We have to find the sum of (6-3x+5y)+(6-3x+5y)^2+..........+(6-3x+5y)^2002, given that 3x - 5y = 7.

Now we see that the terms of the sum are in a GP. The first term is 6 - 3x + 5y and each subsequent term is a product of the previous with 6 - 3x + 5y

As 3x - 5y = 7

=> 6 - 3x + 5y

=> -1

So the required sum is -1 + 1 - 1 + 1...-1^2002.

=> a*(r^(n+1) - 1)/ (r - 1)

=> -1*((-1)^ 2002 - 1)/(-1-1)

=> -1*(1-1)/-2

=> 0

Therefore (6-3x+5y)+(6-3x+5y)^2+..........+(6-3x+5y)^2002 = 0.

Approved by eNotes Editorial Team

Posted on

3x-5y = 7

We need to find the value of the expression:

E = (6-3x+5y) + (6-3x_5y)^2 + ....+ (6-3x+5y)^2002

We will rewrite:

E = ( 6-(3x-5y)) + (6-(3x-5y)^2 + ....+(6-(3x-5y))^2002

Now we know that 3x-5y = 7

==> E = (6-7) + (6-7)^2 + ....+(6-7)^2002

==> E = -1 + (-1)^2 + (-1)^3 + ....+ (-1)^2001+ (-1)^2002

==> E = -1 + 1  -1 + 1 .... + -1 + 1 = 0

Then the values of the expression (6-3x+5y)+(6-3x+5y)^2+ ...(6-3x+5y)^2002 = 0

Approved by eNotes Editorial Team

Posted on